Decentralization and public sector delivery of health and education services: The Indian experience - Ajay Mahal; Vivek Srivastava; Deepak Sanan (University of Bonn, Center for Development Research (ZEF), 2000)
The paper has two main objectives. The first is to trace the progress in the process of decentralisation in the provision of public services in India. The second is to test the hypothesis that decentralisation in the system of public service delivery in primary health care and education led to improved outcomes for the rural Indian population. Before 1992, with few exceptions, there was little movement towards decentralisation. Rural local bodies functioned primarily as program executing agents for government line departments, with little control over finances, administration, or the pattern of expenditure. The only decentralisation that existed was in the importance of state governments vis-à-vis the centre. After the 1992 Constitutional Amendments, significant progress has taken place in the form of the passing of conformity legislation by state governments, the setting up of State Finance Commissions to examine the distribution of resources from states to local bodies, and accelerated moves towards transfer of planning and expenditure responsibilities to village bodies. The paper used data from the 1994 NCAER survey to test the hypothesis that increased decentralisation/democratisation positively influences enrolment rates and child mortality once the influence of socioeconomic circumstances, civil society organisations, the problem of capture of local bodies by elite groups, and so on are controlled for. Our main empirical findings are that indicators of democratisation and public participation, such as frequency of elections, presence of non-governmental organisations, parent-teacher associations and indicator variables for decentralised states generally have the expected positive effects, although these are not always statistically indistinguishable from zero. – – Die vorliegende Arbeit analysiert zwei Aspekte der dezentralisierten Bereitstellung öffentlicher Güter in Indien. Der erste Teil veranschaulicht den Prozeß der Dezentralisierung, während im zweiten Teil die Hypothese getestet wird, daß eine dezentralisierte Bereitstellung von medizinischer Grundversorgung und Schulen zu einer Verbesserung der Rahmenbedingungen der indischen Landbevölkerung geführt hat. Im Zuge der Verwaltungsreform 1992 wurden den ländlichen Organen zunehmend Aufgaben übertragen. Durch die entsprechende Verfassungsänderung wurde ein fiskalischer Föderalismus eingeführt, der den Gemeinden und Kreisen auch nötige finanzielle Unabhängigkeit verschaffte. Der empirischen Analyse liegen die Daten der NCAER - Erhebung aus dem Jahre 1994 zugrunde. Die Hypothese des positiven Einflusses der Dezentralisierung auf Sterblichkeitsrate und Schülerzahlen wird um die sozioökonomischen Rahmenbedingungen ergänzend überprüft. Die Ergebnisse deuten auf einen positiven Einfluß der verwandten Variablen hin, wobei dieser Einfluß z.T. jedoch gering ausfällt.
Keywords: 330; Dezentralisierung; Gesundheitsversorgung; Allgemeinbildende Schule; Armutspolitik; Wirkungsanalyse; Ländliche Entwicklung; Schätzung; Indien